The Collaborative Role of Stakeholders in the Policy to Stop Open Defecation in Petamburan Subdistrict, Central Jakarta - Rosita Rosita; Firman Hadi Rivai (Green Publisher Indonesia, 2026)
Sanitation remains a critical public health challenge in densely populated urban areas of Indonesia. The purpose of this study is to investigate and identify the role of stakeholders, particularly in Petamburan Village, DKI Jakarta Province, in implementing the Stop Open Defecation (SBS) policy. The method used is qualitative, employing 1) an observation approach, including both direct and indirect observations, and 2) a literature review of policies and references related to Stop Open Defecation (SBS). The results of this research are expected to serve as a reference for enhancing collaboration among stakeholders in harmonizing policy implementation, particularly in preventing open defecation, to achieve a clean, healthy, and comfortable environment for residents. This study concludes that the problem of open defecation in Petamburan is systemic, requiring integrated multi-stakeholder interventions. Collaboration among government, community, and the private sector remains suboptimal, often characterized by top-down approaches without fully leveraging citizen participation. Key contributing factors include limited land availability, economic constraints, and low levels of sanitation education.